Network analysis of primary health care centers using numerical simulation and genetic algorithms (AACINI - International Journal of Industrial Engineering, 2024)
The networks of Primary Health Care Centers (PHCC) are an important part of the public health system of our country. In order to maximize the population's access to health goods and services provided in the PHCC, the municipalities make a permanent effort to adapt these networks to the demographic and territorial growth of the cities. This complex problem involves distributing appropriately the number of centers in the territory, with the proper capacity for each type of service offered. The main objective of this work is to study the need, demand, and supply of primary health care services using a mathematical model. For the specific case study of a medium-sized city territorially disaggregated into census cells, firstly, the current system situation is investigated through simulation using a simple model of willingness to move. Next, the effect of modifying the capacity of services in existing PHCC is analyzed. Finally, the impact of incorporating new centers into the network is investigated in order to maximize the estimated demand using a genetic algorithm. The proposed methodology makes it possible to systematically study the system with the available information and analyze the impact of changes in services’ offering on the main access indicators.
Keywords: Need-Supply-Demand; Genetic Algorithm; PHCC